Capabilities for Innovation: The Nordic Model and Employee Participation - Nielsen, Peter; Nielsen, René Nesgaard; Bamberger, Simon Grandjean; Stamhus, Jørgen; Fonager, Kirsten; Larsen, Anelia; Vinding, Anker Lund; Ryom, Pia; Omland, Øyvind (Nordic Journal of Working Life Studies, 2012)
Technological developments combined with increasing levels of competition related to the ongoing globalization imply that firms find themselves in dynamic, changing environments that call for dynamic capabilities. This challenges the internal human and organizational resources of firms in general and in particular their ability to develop firm-specific innovative capabilities through employee participation and creation of innovative workplaces. In this article, we argue that national institutional conditions can play an enhancing or hampering role in this. Especially the norms and values governing relations between employers and employees are expected to be of vital importance. This article will follow a resource-based perspective on developing dynamic capabilities in order to test the importance of enhancing human and organizational capabilities for innovation in firms. In particular, the article will focus on some of the important institutional conditions in Danish firms derived from the Nordic model, such as the formal and informal relations of cooperation between employers and employees in firms and their function in building capabilities for innovation. The foundation of the empirical analysis is a survey that collected information from 601 firms belonging to the private urban sector in Denmark. The survey was carried out in late 2010.